Post Traumatic Stress Disorder Tokoh Aku dalam Novel Asybahul Jahim Karya Yasmina Khadra Tinjauan Psikologi Sastra - Annastasiah Fridah; Faradiela Qolbi (Universitas Muhammadiyah Gorontalo, 2022)
The articel was conducted to analyze the forms of Post Traumatic Stress Disorder that my character experienced in Yasmina Khadra's novel Asybaḥul jaḥĪm. The study resulted in the conclusion first, that the character of I in Yasmina Khadra's novel Asybaḥul jaḥĪm underwent Post Traumatic Stress Disorder (PTSD). Second, through an analysis of the approach to literary psychology with Kaplan & Sadock theory, several important things have been found, among other things, there have been causes that led to the character I experienced PTSD in the novel, such as, Sulaiman's death, Haitem family events and insults to the family of my figures. Third, some characteristics of someone experiencing PTSD according to Kaplan and Sadock are found in the novel, among others, a) The Figure I see, hear, and even experience some events related to serious injury or death, as well as receiving threats to the physical integrity of himself or the person around him. b) The reaction of the character I involve fear and helplessness, c) The character I experience a recurring dream of the tragedy that inflicts suffering, etc. Fourth, there were found some attempts by my character to exit the PTSD he experienced, such as leaving Kafr Karam who was none other than his hometown, seeking new life in Baghdad and joining the resistance group.